Modelling turnover intention among frontline employees in the Malaysian retail and services industry - Goh, Lin Kin (2019)
Problem in retaining frontline employees especially in the retail and services industry has continuously been a subject of concern to both academicians and practitioners in developed and developing countries since the employees' turnover rate is high. According to ILMIA, the retail and services industry’s turnover rate in Malaysia is gradually increasing; thus, creating serious concerns on efforts to retain frontline employees in this industry. Hence, this study was conducted to look into the extent organizational commitment, transformational leadership and organizational culture influence the turnover intention of employees in the Malaysian retail and services industry, by using the Theory of Reasoned Action (TRA) as the underpinning theory. In fact, this study also looked into organizational commitment as a mediator. The study conducted the confirmatory factor analysis and the model fit analysis via AMOS. The respondents were employees of the Malaysia Retail Chain Association members. Six companies were involved in the study with 389 respondents. The study utilized the simple random sampling technique, in the survey. The findings revealed that all the variables were tested with acceptable normality that permitted the researcher to use AMOS as an analysis tool. The result revealed significant relationships among the variables; whilst organizational commitment was a possible mediator. The model fit analysis proved to be good, displaying significant p-value, entailed with a strong pattern matrix for the constructs’ dimensions. The theoretical contribution of the study is that it shows strong linkages and influences of the four constructs toward each other in one single model, and demonstrates the understanding of the extent of prediction variables on turnover intention. The practical contribution is that it reveals a possible solution involving transformational leaders, emphasizing organizational commitment and acclimatizing the organizational culture in the retail and services industry scenario in order to reduce employees’ turnover, to improve performance and to reduce recruitment and training costs.